RELATIONSHIP BETWEEN BODY IMAGE AND DIET BEHAVIOR IN ADOLESCENT GIRLS AT SENIOR HIGH SCHOOL 2 TAMBUN UTARA IN 2022 - Yana Apriyani Rindi Antika; Arabta M. Peraten Pelawi; Kiki Deniati (Jurnal Medicare, 2023)
Body image is a collection of conscious and unconscious attitudes that individuals have towards their bodies. Includes past and present perceptions and feelings about size, function, appearance, and potency. Body image is more often associated with women than men because women tend to pay more attention to their appearance. Physical changes experienced by adolescents cause changes in body image perceptions.This study aims to determine the relationship between body image and dietary behavior in adolescents at SMA Negeri 2 Tambun Utara in 2022.The research method used is quantitative with a cross-sectional type of research. The population in this study were teenagers in grades X and XI at SMA Negeri 2 Tambun Utara and a sample of 177 female students. Data collection technique using Strativied Random Sampling technique. Statistical test using chi square test with the results of respondents who have a positive body image as many as 41 respondents (23.16%) and respondents who have a healthy diet as many as 98 respondents (55.4%) obtained p value (0.000) < value (0.05). There is a relationship between body image and dietary behavior in adolescent girls at SMA Negeri 2 Tambun Utara in 2022.